Managing Digital Technologies and Soft Skills to Enhance Graduate Employability: The Mediating Role of Psychological Well-Being in Higher Education - Efrita Norman; Melly Nuryani; Enah Pahlawati; Lina Marliani (Al-Qalam Institue, 2026)
This study aims to synthesize empirical evidence on the relationships among Industry 4.0–driven digital technologies, soft skills development, psychological well-being, and graduate employability in higher education, with particular attention to mediating and moderating mechanisms. A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines using the Scopus database, applying inclusion criteria related to publication year (2020–2025), document type, language, subject area, and relevance, resulting in 21 empirical studies analyzed through thematic analysis. The findings indicate that digital technologies function as conditional enablers of soft skills, demonstrating stronger effects when embedded in experiential and participatory pedagogies; digital learning environments also show ambivalent effects on psychological well-being, enhancing engagement when well designed but generating stress when pedagogical and organizational support is inadequate. Furthermore, soft skills consistently emerge as dominant predictors of employability beyond technical skills alone, while psychological well-being plays a crucial mediating role in the relationship between digital technologies, soft skills, and career outcomes, with leadership, organizational culture, and learning ecosystems acting as key moderating factors. These findings imply that higher education institutions must adopt integrated educational management strategies that balance digital innovation with soft skills development and psychological well-being to sustainably enhance graduate employability in the Industry 4.0 era